MEASURING THE INFLUENCE OF TAX ADVERTISING AND SERVICES AS EXTERNAL FACTORS ON TAXPAYER COMPLIANCE - Eko Retno Indriyarti; Michael Christian (Universitas Bunda Mulia, 2021)
ABSTRACT: Amid the continuing increase in the number of taxpayers in Indonesia, it is expected that the amount of tax revenue for the state will continue to increase. The increase in the amount of revenue is aimed at optimizing tax functions, namely budgetary, distribution and stability functions. However, the success of this tax revenue is strongly influenced, one of which is the taxpayer compliance to fulfill its obligations. Apart from internal factors that come from individual taxpayers, external factors have an important role in shaping taxpayer compliance. Several studies still show different results on these external factors on their influence on Taxpayer Compliance. This study aims to explain and analyze the influence of tax and tax service advertisement socialization factors on taxpayer compliance in Jakarta. This research is a quantitative study using multiple regression analysis. The analytical tool used in this study is the Social Package for the Social Sciences (SPSS 25.0). The results of this study explain that taxpayer compliance is influenced by tax advertising socialization. In addition, the Taxpayer Compliance variable is also influenced by tax services. Simultaneously, tax dissemination and services also affect taxpayer compliance. With limitations on the specifications of the external factors used, this study also emphasizes the characteristics of taxpayers such as novice taxpayers, which is an interesting input to be carried out in subsequent studies. The level of tax knowledge for the group taxpayers will be closely related to the awareness of taxpayers in carrying out their obligations. This has an indirect impact on the level of compliance as a taxpayer. Keywords: Taxpayer compliance, advertising, services ABSTRAK: Di tengah terus meningkatnya jumlah wajib pajak di Indonesia diharapkan dapat terus meningkatkan jumlah penerimaan pajak bagi negara. Peningkatan jumlah penerimaan ini bertujuan untuk mengoptimalkan fungsi-fungsi pajak yaitu fungsi budgeter, distribusi, dan stabilitas. Namun demikian keberhasilan penerimaan pajak ini sangat dipengaruhi salah satunya dari Kepatuhan Wajib Pajak untuk memenuhi kewajibannya. Selain faktor internal yang berasal dari individu wajib pajak, faktor eksternal memiliki peran penting dalam membentuk kepatuhan wajib pajak. Beberapa penelitian masih menunjukkan hasil yang berbeda pada faktor-faktor eksternal tersebut terhadap pengaruhnya pada Kepatuhan Wajib Pajak. Penelitian ini bertujuan untuk menjelaskan dan menganalisis pengaruh faktor sosialisasi iklan pajak dan layanan pajak terhadap Kepatuhan Wajib Pajak di Jakarta. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan analisis regresi berganda. Alat analisis yang digunakan pada penelitian ini yaitu Social Package for the Social Sciences (SPSS 25). Hasil penelitian ini menjelaskan bahwa Kepatuhan Wajib Pajak dipengaruhi oleh Sosialisasi iklan pajak. Selain itu, variabel Kepatuhan Wajib Pajak juga dipengaruhi oleh Layanan pajak. Secara simultan, Sosialisasi dan Layanan pajak turut mempengaruhi Kepatuhan Wajib Pajak. Dengan keterbatasan pada spesifikasi faktor eksternal yang digunakan, penelitian ini menekankan juga pada karakter-karakter wajib pajak seperti Wajib Pajak pemula menjadi salah satu masukan yang menarik untuk dilakukan pada penelitian berikutnya. Tingkat pengetahuan pajak bagi wajib pajak kelompok tersebut akan sangat berhubungan dengan kesadaran wajib pajak dalam menjalankan kewajibannya. Hal ini secara tidak langsung berdampak pada seberapa tinggi kepatuhan sebagai Wajib Pajak.Kata Kunci: kepatuhan wajib pajak, iklan, layanan